Selection of experimental strawberry clones for fruit appearance attributes - Souza, Douglas Correa de; Ossani, Paulo César; Costa, Aline Silva; Guerra, Thiago Sampaio; Araújo, Ana Luisa; Resende, Francisco Vilela; Resende, Luciane Vilela (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to carry out the morphological characterization of strawberry fruit of different genotypes, as well as to verify their postharvest conservation. Six commercial cultivars (Albion, Aromas, Dover, Festival, Pircinque, and San Andreas) and nine experimental clones (MDA01, MDA19, MDA22, MDA23, MCA89, MCA94, MFA443, MOGSC468, and MFA443PR) were evaluated. Fruit were produced on semi-hydroponic gutters in protected cultivation and classified according to size, shape, color, brightness, achene position, pulp color, “heart” color, fruit cavity, and sepal position. For the postharvest analysis of fruit, the loss of mass and the appearance of fruit during ten days of storage were determined. The evaluated genotypes show a high similarity to each other regarding morphological characterization. MCA89 and 'Pircinque' are the most divergent genotypes in relation to the others. There is an association between the characteristics large cavity, reniform shape, and medium cavity, which contributes to the indirect selection of desirable characters. On the tenth day of storage, the MDA01, MDA19, MCA89, MFA443, and 'Dover' genotypes still show acceptable conditions for commercialization.